2020
DOI: 10.5194/angeo-38-123-2020
|View full text |Cite
|
Sign up to set email alerts
|

Magnetospheric Multiscale observations of energetic oxygen ions at the duskside magnetopause during intense substorms

Abstract: Abstract. Energetic oxygen ions (1–40 keV) observed by the Magnetospheric Multiscale (MMS) satellites at the duskside magnetopause boundary layer during phase 1 are investigated. There are 57 duskside magnetopause crossing events identified during intense substorms (AE>500 nT). These 57 events of energetic O+ at the duskside magnetopause include 26 events during the expansion phase and 31 events during the recovery phase of intense substorms. It is found that the O+ density in the duskside magnetopause boun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…These IMF By effects on O + spatial distribution are finally reflected in the dayside magnetopause. In a companion paper by Zeng et al (2020), the dependence of O + abundance on the IMF directions for intense substorm (AE > 500 nT) are investigated. The results showed that the O + /H + density ratio at the duskside magnetopause boundary layer exponentially increases with IMF By increasing from −5 to 8 nT during intense substorm.…”
Section: Discussionmentioning
confidence: 99%
“…These IMF By effects on O + spatial distribution are finally reflected in the dayside magnetopause. In a companion paper by Zeng et al (2020), the dependence of O + abundance on the IMF directions for intense substorm (AE > 500 nT) are investigated. The results showed that the O + /H + density ratio at the duskside magnetopause boundary layer exponentially increases with IMF By increasing from −5 to 8 nT during intense substorm.…”
Section: Discussionmentioning
confidence: 99%